The effect of Inclusive Intervention Programme on the attitudes of Tertiary Students toward Inclusion in Singapore - Nonis, Karen; Cho, Edwin; Padmanabhan, Uma (IASE International, 2019)
The purpose of this study was to develop an understanding as to whether tertiary student’s participation in a course about inclusive education would influence their attitudes towards inclusion. Three hundred students (16 to 20 years) from a Polytechnic participated in the study in Singapore. Phase 1 involved a demographic survey and an adapted survey about attitudes toward inclusion Phase Two was the 13 week Intervention Programme and a post survey. The authors discuss the impact of Intervention on student’s attitudes.